Postgres Server Developer Bruce Momjian Discusses Multiversion Concurrency Control - Blumen, Robert; Blumen, Robert (IEEE software, 2022)
Presents an interview conducted with Postgres server developer Bruce Momjian who discusses multiversion concurrency control (MVCC) in the Postgres database.